Sabino Canyon : The Life of a Southwestern Oasis - Lazaroff, David Wentworth, 1948- (Book collections on Project MUSE., 1993)
A popular guide to the natural and human history of a verdant canyon at the edge of the desert outside Tucson, Arizona. Many fine color plates and lucid drawings.